Republic of Serbia : 2021 Article IV Consultation and Request for a 30-Month Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Republic of Serbia. (IMF Staff Country Reports; Country Report, 2021)
Recent economic developments. Supported by a large policy package, Serbia's economy rebounded quickly from the initial COVID-19 shock, recording a 1 percent contraction of real GDP in 2020. Job losses have mostly been contained to the informal sector, thanks to policy measures aimed at preserving formal employment. A supplementary budget for 2021 was adopted in April boosting capital expenditure and extending policy support to households and corporates, against the background of third and fourth waves of infections and related containment measures, as well as a weaker-than-expected economic recovery in key trading partners. Inflation remains low. After rising again in late February, infections tapered, helped by new containment measures and the rapid vaccine rollout.